Increasing Ketamine Use for Refractory Status Epilepticus in US Pediatric Hospitals. (June 2017) - Keros, Sotirios; Buraniqi, Ersida; Alex, Byron; Antonetty, Annalee; Fialho, Hugo; Hafeez, Baria; Jackson, Michele C.; Jawahar, Rachel; Kjelleren, Stephanie; Stewart, Elizabeth; Morgan, Lindsey A.; Wainwright, Mark S.; et al.
Ketamine is an emerging therapy for pediatric refractory status epilepticus. The circumstances of its use, however, are understudied. The authors described pediatric refractory status epilepticus treated with ketamine from 2010 to 2014 at 45 centers using the Pediatric Hospital Inpatient System database. For comparison, they described children treated with pentobarbital. The authors estimated that 48 children received ketamine and pentobarbital for refractory status epilepticus, and 630 pentobarbital without ketamine. Those receiving only pentobarbital were median age 3 [interquartile range 0-10], and spent 30 [18-52] days in-hospital, including 17 [9-28] intensive care unit (ICU) days; 17% died. Median cost was 148 000 [81 000-241 000]. The pentobarbital-ketamine group was older (7 [2-11]) with longer hospital stays (51 [30-93]) and more ICU days (29 [20-56]); 29% died. Median cost was 298 000 [176 000-607 000]. For 71%, ketamine was given ≥1 day after pentobarbital. Ketamine cases per half-year increased from 2 to 9 ( P < .05). Ketamine is increasingly used for severe pediatric refractory status epilepticus, typically after pentobarbital. Research on its effectiveness is indicated.